2007
DOI: 10.4278/0890-1171-21.5.460
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Obesity and Injuries among U.S. Adults

Abstract: Our findings show a clear association between BMI and the probability of sustaining an injury. If increasing BMI is causing the rise in injury rates, then the incidence of injuries, including those related to falls, sprains/strains, lower extremity fractures, and joint dislocations, are likely to increase as the prevalence of obesity increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
95
2
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(116 citation statements)
references
References 27 publications
11
95
2
8
Order By: Relevance
“…The HR for sustaining an injury were 12% (obese class I) to 21% (obese class II) greater among those with excess weight than those with normal weight, which is similar to other studies. 9 In addition, we observed a positive relationship between BMI and injury-related expenditure, possibly because of an increased severity of injury and higher injury frequencies among those obese adults. 3,4 Earlier, a retrospective review study of 316 patients in a Los Angeles County Medical Center found that obese patients had more complications and required longer intensive care unit stays (obese 8±9 days vs non-obese 6±6 days, P ¼ 0.05) after severe trauma.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The HR for sustaining an injury were 12% (obese class I) to 21% (obese class II) greater among those with excess weight than those with normal weight, which is similar to other studies. 9 In addition, we observed a positive relationship between BMI and injury-related expenditure, possibly because of an increased severity of injury and higher injury frequencies among those obese adults. 3,4 Earlier, a retrospective review study of 316 patients in a Los Angeles County Medical Center found that obese patients had more complications and required longer intensive care unit stays (obese 8±9 days vs non-obese 6±6 days, P ¼ 0.05) after severe trauma.…”
Section: Discussionmentioning
confidence: 60%
“…In brief, our findings were generally consistent with the former studies. 9 Regression results by injury types are presented in Table 3. The regression results include the top five injury types: strain/sprain, contusions, open wounds, superficial, fractures, and other injuries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations